TRANSPARANSI INFORMASI PUBLIK DALAM PENYELENGGARAAN PEMILU LEGISLATIF - ', Ismail (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Transparency of Public Information in the Implementation of the legislative elections in 2014. Objective was to determine the type of data in the category of public information transparency and barriers to implementation of public information transparency in the implementation of the 2014 legislative elections in the province of Riau. As for the key informants in this study is the Chairman of the Election Commission along with the ranks of Riau province Organic kesektariatan Commission. Susulannya informant is using snowball sampling technique. The technique of collecting data using interviews and documents. Analysis of data using an interactive model. The results showed that overall the 2014 legislative elections run in accordance with the mandate of the Act. Irregularities and obstacles that occur in the form of issue of the capabilities and quality of human resources from the ranks of the organizers who have not been balanced with the workload.